Implementation of the Six Sigma methodology to improve the process performance in a MYPE - Ortiz Velasquez, Cristian Alexander (2024)
Those in charge of directing small and micro companies many see the application of improvement tools as something unnecessary; since, they think that they are complicated development methods that will represent unnecessary expense of time and money, and therefore they prefer to remain in the same situation and do not take advantage of the possibility of improving and growing as an organization. In the development of this research, the influence of the application of the Six Sigma methodology is studied and approached in a practical way; tool that allows to measure the performance of a process for the identification of defects and determine the ideal improvements to apply, in a MYPE. Different articles were analyzed, where the Six Sigma model had been applied; which presented improvements for the organizations to which they were directed. In addition, the Six Sigma methodology was implemented in a MYPE that provided the car wash service; whose process initially had a non-optimal performance, but by implementing the Six Sigma method, improvements were achieved such as: the increase in the availability of the pressure washer machine from 84.31% to 92.78%, the increase in the number of vehicles washed, reduction of 122 hours stopped for maintenance and reduction of rejected vehicles.